O gibalni količini svetlobe v prozornem sredstvu - Strnad, Janez (Obzornik za matematiko in fiziko, 2015)
Apparently, the more as hundred years old dilemma of the momentum of light in a transparent medium, known as the Minkowski-Abraham controversy, is nearing its solution. In the International year of light it seems appropriate to report on this also with respect to new measuring methods.
Keywords: svetloba; gibalna količina; prozorna snov; poskusi; meritve